The Role Of Environmental Sustainability In Design Thinking To Contemporary University Buildings (In Hot- Dry Climates Environments) (Journal of Planner and Development, 2019)
The Architectural Environment Of The University Buildings As The Main Educational Institution Reflecting The Culture And Civilization Of Worthwhile Things To Achieve Communication And Transfer The Cultural Message Generation After Generation, For The Increasing Numbers Of Universities And Its Expansion In The Current Era Of Increasing Numbers Of Students Towards Higher Education With The Increased Problems With Environmental Cases Of Energy Consumption And Increased Economic Cost, Pollution And Water Poverty Especially In Hot- Dry Climates Make University Buildings Are To Suffer To Environmental Problems Of Design, And The Fundamental Characteristic Of University Buildings Are Changing Rapidly And Continuously Repeated Interaction With Context And Their Response To Its Age, The Challenge Is Production Of University Buildings Reduce Energy Consumption And Resources And Depend On Renewable Energy And Water Conservation, Waste Management And The Requirements Of Present Needs And Keep Up With The Future, Requiring The Need For Evolution And Change In The Contemporary University Buildings Design Thought And The Adoption Of Modern Standards Of A New Design Suitable For The Nature Of The Hot Dry Climate, And That Environmental Sustainability Is One Of The Modern Trends In Architectural Thought, Who Cares About The Relationship Between The Buildings And The Environment And To Reduce The Consumption Of Energy Sources And To Transform The University Into A Sustainable Society A Friend Of The Environment, Research Has Identified Problem (Knowledge Limitations On The Role Of Environmental Sustainability In Design Thinking To Contemporary University Buildings In Dry Climates And Their Effectiveness And Potential Environmental Design Solutions To Environmental Problems Afflicting The Universities In The Current Era And Make It Responsive To Future Requirements And Age Data In Light Of Increasing University Buildings And Their Expansion And Increasing Numbers Of Students) Assuming (Environmental Sustainability A Fundamental Role And Directly In Design Thinking To Contemporary University Buildings In Dry Hot Climate In Order To Achieve The Environmental Efficiency Of Buildings That Work To Decrease The Energy Consumption And It’s The Resulting Problems, And Response Of The Needs Age And, Consistent With The Context And Responsive To Future Requirements) The Research Found That Environmental Sustainability And Apply Their Strategies As The Thought Of Design For Contemporary University Buildings In Hot- Dry Climates Is Active Role In Design Solutions For Environmental Problems In University Buildings Today And Make Them Compatible With Its Surroundings And Keeping Up With Needs The Present Times And Responsive To Community Needs And Future Requirements, Including Choose The Appropriate Site And The Planning And Design Site ,Efficient Transportation And Management Of Resources And Materials And Recycling Of Waste, With The Efficiency Of The Internal Environment And Preserve Natural Sources Of Energy And Environmental Protection, And Protection Water And Its Processed.